HUBUNGAN KEPEMIMPINAN KEPALA SEKOLAH DENGAN KARAKTER SISWA KELAS V SD NEGERI 101799 DELITUA - Edidon Hutasuhut; Shanti Andria Chairani (Universitas Negeri Medan, 2018)
Abstract: Relationship between Principal Leadership and Character ofClass V of State Elementary School 101799 Delitua. This study aims todetermine whether or not there is a Principal Leadership Relationship with theCharacter of Class V Students of State Elementary School 101799 Delitua2017/2018 Academic Year. The benefits of this study are as input that can be usedfor Principals in carrying out leadership in fostering student character and asinformation that can add research insights specifically regarding the Relationship ofPrincipal Leadership with Student Characters. This research is quantitative researchusing correlational techniques, data collection tools in the form of PrincipalLeadership with Student Character questionnaire. Testing is done with a populationof 46 students and a total sampling of 46 students. From the calculation of the datashows that there is a positive and significant relationship between PrincipalLeadership and the Character of Class V Students of State Elementary School101799 Deli Tua T.A 2017/2018.Keywords: Student Character, Principal LeadershipAbstrak: Hubungan Kepemimpinan Kepala Sekolah dengan Karakter SiswaKelas V SD Negeri 101799 Delitua. Penelitian ini bertujuan untuk mengetahui adatidaknya Hubungan Kepemimpinan Kepala Sekolah dengan Karakter Siswa Kelas VSD Negeri 101799 Delitua Tahun Ajaran 2017/2018. Adapun manfaat daripenelitian ini adalah sebagai masukan yang dapat digunakan untuk Kepala Sekolahdalam menjalankan kepemimpinan membina karakter siswa serta sebagai informasiyang dapat menambah wawasan penelitian khususnya mengenai HubunganKepemimpinan Kepala Sekolah Dengan Karakter Siswa. Penelitian ini merupakanpenellitian kuantitatif dengan menggunakan teknik korelasional, alat pengumpulandata berupa angket Kepemimpinan Kepala Sekolah dengan KarakterSiswa.Pengujian dilakukan dengan populasi sebanyak 46 siswa dan pengambilansampel secara total sebanyak 46 siswa. Dari hasil perhitungan data menunjukkanbahwa terdapat hubungan yang positif dan signifikan antara Kepemimpinan KepalaSekolah dengan Karakter Siswa Kelas V SD Negeri 101799 Deli Tua T.A2017/2018.Kata Kunci : Karakter Siswa, Kepemimpinan Kepala Sekolah